Design and development of a second order side-channel-attack platform - Liu, Tianlei (2019)
Informatization is an important global trend in the world today. After decades of development, information technology has been permeated and applied into almost all areas. The rapid development of informatization has fundamentally changed the way people live, work, and think. It even has profound influence on the world view of human beings. Nobody could stop this global informatization. On one hand, the modern information technology has already brought huge convenience to people and the quality of life is grew markedly without doubt. However, on the other hand, the high degree of informatization brings many security issues as well. Once important information system is under attack, its catastrophic impact may be unprecedented. For instance, customers data of a bank could be possibly released illegally if hacked by criminals. As a consequent, not only the money but also the privacy will be deprived, which cause uncalculatable losses for customers. Therefore, it is necessary to protect information effectively. Modern cryptography provides us numerous of methods to prevent illegal attacks. It is a study which involves encryption and decryption of information. However, there is no absolute safe cryptographic device or algorithm until now. It could only try the best to minimize the chance which hacker will attack confidential information successfully. Thus, understand different ways of attack will increase reliability of cryptographic devices. Side Channel Attack (SCA) is one of popular methods which is commonly used for breaking cryptographic device. This dissertation report shows not only fundamentals related to SCA, but also demonstrates the design and development of a second order SCA platform. Simulation and its results are displayed in chapter 7.